Use of Mobile Technologies in the Healthcare Industry and Business: The Case of Pulmonary Function or Breathing Test Supportive Care - Alreisi, Amir; Moghaddas, Raziyeh (Journal of business, communication and technology, 2023)
Digital spirometry, which is used to monitor and diagnose both acute and chronic lung diseases, has been the subject of research for many years. This research undertakes the initiative to build a novel mobile-based digital spirometry application helpful in diagnosing diseases such as asthma and Chronic Obstructive Pulmonary Disease (COPD). As part of the application’s design, it consists of hardware and software components, including a pipe in which the user can breathe into, a pressure sensor that helps to collect patients’ breaths, an Arduino board that is be responsible for processing patients’ breaths received form the pressure sensor and convert the signal to the MIDI (Musical Instrument Digital Interface) message readable by the mobile application, and finally a spirometry application developed using android studio, JAVA programming language, as a user interface. Furthermore, the database applied in this project is SQLite which utilizes cloud-based storage technology rather than server-based models which might be costly. All parts work as a circuit unit that is capable of monitoring the user’s breathing system, and processing to provide an appropriate report of its performance. According to the findings, digital spirometry based on mobile application and MIDI protocol is practical and offers all the fundamental metrics that are supported by conventional spirometers.